2013
DOI: 10.5455/2319-2003.ijbcp20130315
|View full text |Cite
|
Sign up to set email alerts
|

Drug utilization study of co-administration of nonsteroidal anti-inflammatory drugs and gastroprotective agents in an orthopaedics outpatients department of a tertiary care hospital in West Bengal

Abstract: Background: Non steroidal anti-inflammatory drugs (NSAIDs) are the commonly prescribed analgesic in the orthopaedics department. NSAIDs are prescribed for a long period in both acute condition (like fracture of bones, muscle injury, postoperative procedures etc) or chronic conditions (osteoarthritis etc). However, they have many adverse effects, especially gastrointestinal toxicity when use regularly. For this reason NSAIDs are frequently co-prescribed with gastro protective agents. Common gastroprotective age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…2 Drug utilization studies are continuing programmes that review, analyze and interpret the pattern of drug use. 3 These studies are also helpful to suggest modifications, if necessary, in the prescribing behavior of medical practitioners to make medical care rational and cost effective. 4 This study was conducted to observe and analyze the prescribing pattern of drugs for the in-patients in the general medicine department of a teaching hospital.…”
Section: Introductionmentioning
confidence: 99%
“…2 Drug utilization studies are continuing programmes that review, analyze and interpret the pattern of drug use. 3 These studies are also helpful to suggest modifications, if necessary, in the prescribing behavior of medical practitioners to make medical care rational and cost effective. 4 This study was conducted to observe and analyze the prescribing pattern of drugs for the in-patients in the general medicine department of a teaching hospital.…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted by Ajay Kumar et al, in an orthopedics outpatients department of a tertiary care hospital in West Bengal, Famotidine (46.12%) was the most frequently used gastroprotective co-administered with non-steroidal anti-inflammatory drugs [12] . Several studies revealed that around 70% of patients admitted to nursing facilities or being hospitalized were on acid suppressive medication with more than 50% of them without an appropriate diagnosis justifying prescription [ 13,14] Another major health concern is the current inappropriate self-medication habit.…”
Section: Fig-1: Gastro Protective Drugs Prescribed With Other Drugsmentioning
confidence: 99%
“…2,3 NSAIDs are also most widely prescribed class of medications worldwide and commonly used over the counter. 4 These drugs have a wide range of adverse effects. Gastrointestinal toxicity is a major clinical limitation.…”
Section: Introductionmentioning
confidence: 99%